Modified Semilunar Advanced Flap with Connective Tissue Graft Technique for Root Coverage: A Case Report - Anurag Satpathy1, Bhagyashree Lenka2, Rinkee Mohanty3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Gingival recession may not only result in aesthetically unacceptable results but also be associated withincreased susceptibility to root caries and dentinal hypersensitivity. A novel technique for recessioncoverage by using a modified semilunar advanced flap technique with connective tissue graft is described.The technique involves placing of connective tissue graft underneath a semilunar incision which is madeparallel to the free gingival margin of the facial tissue and its advancement over the denuded root. Thistechnique has the advantage over conventional semilunar flap, in that benefit of connective tissue graft iscombined for improved prognosis